Liquid phase precipitation synthesis method of aluminum salt type lithium ion adsorbent

The lithium ion adsorbent is synthesized by one-step liquid phase precipitation. The reaction between lithium salt and metaaluminate is solved, and the problems of low lithium ion adsorption capacity and complex process in the prior art are achieved, thus achieving efficient and low-carbon adsorbent production , improves adsorption-desorption efficiency and lithium selectivity.

CN115837266BActive Publication Date: 2025-01-14BYD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111101864.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-18
Publication Date
2025-01-14
Estimated Expiration
2041-09-18

AI Technical Summary

Technical Problem

The existing aluminum salt type lithium ion adsorbent has low lithium ion adsorption capacity and complex synthesis process, making it difficult to achieve large-scale industrial production, and has large carbon emissions and low desorption efficiency.

Method used

The lithium ion adsorbent precursor was synthesized by a one-step liquid phase precipitation method, and the pH value and stirring conditions were controlled by a mixing reaction between lithium salt and metaaluminate, and multiple rounds of filtration and pre-desorption treatment were carried out to obtain a high specific surface area and pores adsorbents with high lithium ion adsorption capacity.

Benefits of technology

It realizes efficient production of lithium ion adsorbents, simplifies the process flow, reduces energy consumption and carbon emissions, improves adsorption-desorption efficiency and lithium selectivity, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003271232870000131
    Figure BDA0003271232870000131
  • Figure BDA0003271232870000141
    Figure BDA0003271232870000141
  • Figure BDA0003271232870000142
    Figure BDA0003271232870000142
Patent Text Reader

Abstract

The present disclosure relates to a lithium ion adsorbent and a method for preparing the lithium ion adsorbent. The lithium ion adsorbent disclosed herein has a large specific surface area, high porosity, large adsorption capacity, stable adsorbent structure, and good cycle stability. The method for preparing the lithium ion adsorbent disclosed herein is a liquid phase precipitation synthesis method, which has a simple synthesis process, is easy to operate, easy to control, has low energy consumption, high conversion rate in the synthesis process, high lithium utilization rate, high production efficiency, and is energy-saving and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of chemistry, and in particular, to an aluminum salt type lithium ion adsorbent and a liquid phase precipitation synthesis method of the aluminum salt type lithium ion adsorbent. Background Art

[0002] At present, the method for synthesizing aluminum salt type lithium ion adsorbent mainly includes: mixing AlCl3 and LiCl solution and slowly adding NaOH solution to react, while generating Al(OH)3, Li + Embedded into the interlayer structure of Al(OH)3, thus forming LiCl·2Al(OH)3·nH2O. The adsorbent prepared by this method has a decent adsorption capacity, but three raw materials are required for synthesis, and NaOH is a strong base. The process control of generating Al(OH)3 is difficult, the pH value control requires high requirements, the operation is complicated, and it is difficult to achieve large-scale industrial production. AlCl3 and LiCl solution are mixed and added to the bicarbonate solution, and bicarbonate and aluminum ion are double hydrolyzed to generate aluminum ion adsorbent in one step. The suspension containing LiCl·2Al(OH)3·nH2O is obtained by heating reaction, and the adsorbent is obtained after solid-liquid separation. This method also requires the use of three raw materials for synthesis, and a large amount of CO2 is discharged during the synthesis process, and the carbon emission is too large. Al(OH)3 particles are placed in LiOH solution, so that LiOH is immersed in the gaps of Al(OH)3 particles, and then HCl is added to adjust the pH value of the solution. After aging treatment, LiCl·2Al(OH)3·nH2O is finally formed. The adsorbent prepared by this method has low adsorption capacity and low desorption efficiency, and requires higher temperature and longer time for desorption.

[0003] The lithium ion adsorption capacity of the adsorbent obtained by the above method is still low. Summary of the invention

[0004] The purpose of the present disclosure is to provide a lithium ion adsorbent and a method for preparing the lithium ion adsorbent, which can overcome the current problem of low lithium ion adsorption capacity.

[0005] The inventors of the present disclosure discovered that the adsorbent precursor can be synthesized by a one-step liquid phase precipitation method, the synthesis process is simple, and industrial production can be easily realized, thus obtaining the present disclosure.

[0006] In order to achieve the above-mentioned object, the first aspect of the present disclosure provides a lithium ion adsorbent, wherein the lithium ion adsorbent contains a substance having a chemical formula of LiCl·2Al(OH)3·nH2O, wherein n is an integer of 1-3;

[0007] The specific surface area of ​​the lithium ion adsorbent is 20-36m 2 / g, preferably 33-36m 2 / g;

[0008] The average pore diameter of the lithium ion adsorbent is 20-35 nm, preferably 22-24 nm;

[0009] The total pore volume of the lithium ion adsorbent is 0.15-0.32 mL / g, preferably 0.28-0.32 mL / g;

[0010] The D10 of the lithium ion adsorbent is 3-12 μm, preferably 3-6 μm;

[0011] The D50 of the lithium ion adsorbent is 12-22 μm, preferably 12-16 μm;

[0012] The D90 of the lithium ion adsorbent is 20-40 μm, preferably 20-29 μm.

[0013] Optionally, the lithium ion adsorption capacity of the lithium ion adsorbent is 3-10 mg / g, preferably 8-10 mg / g; the lithium ion desorption rate of the lithium ion adsorbent is 95-100%, preferably 98-99%;

[0014] When the lithium ion adsorbent is used for adsorbing lithium ions in brine containing magnesium and lithium, the mass ratio of magnesium to lithium in the brine to the mass ratio of magnesium to lithium in the desorption solution is 18-68:1;

[0015] In the lithium ion adsorbent, the content of the substance with the chemical formula of LiCl·2Al(OH)3·nH2O is 95-100 weight %.

[0016] A second aspect of the present disclosure provides a method for preparing a lithium ion adsorbent, the method comprising the following steps:

[0017] S1. Adding a lithium salt solution to an aluminate solution, or adding an aluminate solution to a lithium salt solution, and then performing a first stirring, a first aging and a first filtration to obtain a precursor having a chemical formula of LiOH·2Al(OH)3·nH2O, where n is an integer of 1-3; S2. Mixing the precursor with an acid, and controlling the amount of the acid added so that the pH value of the mixed material is 6.0-7.0, and then performing a second stirring, a second aging and a second filtration to obtain a filtrate from a second filtration; S3. Subjecting the filtrate from the second filtration to 1 to 3 rounds of pre-desorption-filtration cycle treatment.

[0018] Optionally, in step S1, the concentration of the lithium salt solution is 0.5-5 mol / L, preferably 4-5 mol / L, the concentration of the aluminate solution is 0.5-2 mol / L, preferably 1.5-2 mol / L; the molar ratio of Li in the lithium salt to Al in the aluminate is 1-1.3:2;

[0019] When the lithium salt solution is added to the aluminate solution, the aluminate solution is stirred at 100-500 rpm, and the lithium salt solution is added at a flow rate of 0.02-5 L / min, and the amount of the lithium salt solution added is 0.05-2.6 L per liter of the aluminate solution;

[0020] When the metaaluminate solution is added to the lithium salt solution, the lithium salt solution is stirred at 100-500 rpm, and the metaaluminate solution is added at a flow rate of 0.02-5 L / min, and the amount of the metaaluminate solution added is 0.38-20 L per liter of the lithium salt solution;

[0021] The first stirring conditions include: stirring time of 30-120 min, stirring rate of 100-500 rpm, temperature of 10 to 90° C., preferably 40-60° C.;

[0022] The first aging conditions include: temperature of 5-30°C, time of 1-12h, preferably 1-2h;

[0023] The conditions for the first filtration include: the mesh number of the filter cloth is 1000-5000 mesh, and the filtration negative pressure is 0.04-0.07 MPa.

[0024] Optionally, the method further comprises: subjecting the filtrate obtained by the first filtration to 1 to 3 rounds of washing and filtration cycles;

[0025] The filtrate obtained from the first filtration is subjected to 1 to 3 rounds of washing and filtration cycles before being mixed with the acid; and / or,

[0026] The filtrate obtained by the second filtration is subjected to 1 to 3 rounds of washing and filtration cycle treatment before the pre-desorption-filtration cycle treatment;

[0027] The washing and filtering cycle treatment includes a first washing and a fourth filtration performed in sequence, wherein the first washing is accompanied by stirring; the conditions of the first washing include: a temperature of 5-30°C, a time of 3-15min, a stirring rate of 100-300rpm, and a weight ratio of the filtrate obtained by the first filtration to pure water of 1:5-50; the conditions of the fourth filtration include: a filter cloth mesh number of 1000-5000 meshes, and a filtration negative pressure of 0.04-0.07MPa.

[0028] Optionally, in step S2, the concentration of the acid is 0.5-3 mol / L;

[0029] The second stirring conditions include: stirring time of 30-120 min, stirring rate of 100-500 rpm;

[0030] The second aging conditions include: temperature of 5-30°C, time of 1-12h, preferably 11-12h;

[0031] The conditions for the second filtration include: the mesh number of the filter cloth is 1000-5000 mesh; and the filtration negative pressure is 0.04-0.07 MPa.

[0032] Optionally, in step S3, the pre-desorption-filtration cycle treatment step includes performing pre-desorption and third filtration once, and the pre-desorption conditions include: the weight ratio of the second filtrate to the pre-desorbed pure water is 1:5-100; the pre-desorption treatment is accompanied by stirring; the temperature is 30-50°C, the time is 2-6h, and the stirring rate is 100-500rpm;

[0033] The conditions of the third filtration include: the mesh number of the filter cloth is 1000-5000 mesh; the negative pressure of the filtration is 0.04-0.07MPa;

[0034] Optionally, the lithium removal amount of the pre-desorption-filtration cycle treatment is 50-80%.

[0035] Optionally, the method further comprises: drying the filtrate obtained from the pre-desorption-filtration cycle treatment.

[0036] Optionally, the drying conditions include: a temperature of 70-90° C. and a time of 120-180 min.

[0037] Through the above technical scheme, the method disclosed in the present invention can generate an adsorbent precursor through a one-step method of lithium salt and aluminate, with high conversion rate, easy to control, and can produce an adsorbent with good adsorption performance in a relatively short period of time, with high production efficiency. The synthesis process of the method disclosed in the present invention has only simple steps such as mixing precipitation, stirring and washing, and filtering, and does not require complex equipment. It is easy to operate, easy to control, and has low investment in production equipment. The process of synthesizing an adsorbent precursor by a one-step method of liquid phase precipitation disclosed in the present invention has a simple synthesis process and is easy to realize industrial production. In addition, the liquid phase synthesis process disclosed in the present invention is low-carbon, energy-saving and environmentally friendly. The entire synthesis process is green and environmentally friendly, with no pollutant emissions, and an adsorbent with excellent performance can be obtained at room temperature. Compared with the high-temperature solid phase method, it has low energy consumption. The lithium ion adsorbent disclosed in the present invention has a large specific surface area, high porosity, high adsorption-desorption efficiency, and large adsorption capacity; furthermore, the lithium ion adsorbent disclosed in the present invention has a small pore size and high lithium selectivity; furthermore, the lithium ion adsorbent disclosed in the present invention has a stable structure and good cycle stability; furthermore, the lithium ion adsorbent disclosed in the present invention has a high conversion rate in the synthesis process, a high lithium utilization rate, and high production efficiency.

[0038] Other features and advantages of the present disclosure will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0039] The following is a detailed description of the specific embodiments of the present disclosure. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.

[0040] A first aspect provides a lithium ion adsorbent, wherein the lithium ion adsorbent contains a substance with a chemical formula of LiCl·2Al(OH)3·nH2O, wherein n is an integer of 1-3.

[0041] The specific surface area of ​​the lithium ion adsorbent can be 20-36m 2 / g, preferably 33-36m 2 / g.

[0042] The average pore diameter of the lithium ion adsorbent may be 20-35 nm, preferably 22-24 nm.

[0043] The total pore volume of the lithium ion adsorbent may be 0.15-0.32 mL / g, preferably 0.28-0.32 mL / g.

[0044] The D10 of the lithium ion adsorbent may be 3-12 μm, preferably 3-6 μm.

[0045] The D50 of the lithium ion adsorbent may be 12-22 μm, preferably 12-16 μm.

[0046] The D90 of the lithium ion adsorbent may be 20-40 μm, preferably 20-29 μm.

[0047] Optionally, the lithium ion adsorption capacity of the lithium ion adsorbent may be 3-10 mg / g, preferably 8-10 mg / g; the lithium ion desorption rate of the lithium ion adsorbent may be 95-100%, preferably 98-99%.

[0048] When the lithium ion adsorbent is used for adsorbing lithium ions in brine containing magnesium and lithium, the ratio of the mass ratio of magnesium to lithium in the brine to the mass ratio of magnesium to lithium in the desorption solution may be 18-68:1.

[0049] In the lithium ion adsorbent, the content of the substance with the chemical formula of LiCl·2Al(OH)3·nH2O is 95-100 weight %.

[0050] A second aspect of the present disclosure provides a method for preparing a lithium ion adsorbent, the method comprising the following steps:

[0051] S1. Adding a lithium salt solution to an aluminate solution, or adding an aluminate solution to a lithium salt solution, and then performing a first stirring, a first aging and a first filtration to obtain a precursor having a chemical formula of LiOH·2Al(OH)3·nH2O, where n is an integer of 1-3; S2. Mixing the precursor with an acid, performing a precursor conversion treatment, and controlling the amount of the acid added so that the pH value of the mixed material is 6.0-7.0, and then performing a second stirring, a second aging and a second filtration to obtain a second filtered filtrate LiCl·2Al(OH)3·nH2O, where n is an integer of 1-3; S3. Subjecting the second filtered filtrate to 1 to 3 rounds of pre-desorption-filtration cycle treatment.

[0052] The lithium ion adsorbent precursor synthetic material disclosed in the present disclosure may include a lithium salt and aluminate, wherein the lithium salt may be at least one of soluble lithium salts such as lithium chloride, lithium sulfate, lithium nitrate, and lithium acetate; and the aluminum salt may be sodium aluminate or potassium aluminate.

[0053] The lithium salt solution disclosed in the present invention can dissolve at least one of soluble lithium salts such as lithium chloride, lithium sulfate, lithium nitrate, lithium acetate, etc. in pure water at a temperature of room temperature to 90°C and a stirring rate of 100 to 500 rpm until the solution is clear and transparent; the aluminate can dissolve sodium aluminate or potassium aluminate in pure water at a temperature of room temperature to 90°C and a stirring rate of 100 to 500 rpm until the solution is clear and transparent; wherein, the clarity of the solution indicates that the lithium salt or the aluminate is completely dissolved.

[0054] The lithium salt solution is added to the aluminate solution, or the aluminate solution is added to the lithium salt solution, and the mixing method can be any one of the following three mixing methods: Mixing method 1: Under the condition that the temperature of the aluminum salt solution is room temperature to 90°C and the stirring rate is 100-500rpm, the completely dissolved lithium salt solution can be added to the aluminate solution at a flow rate of 0.02-5L / min through a peristaltic pump, and the amount of lithium salt solution added can be 0.05-2.6L per liter of the aluminate solution. After the mixing is completed, stirring is continued, and the stirring conditions may include: the stirring rate can be 100-500rpm, and the time can be 30-120min; Mixing method 2: Under the condition that the temperature of the lithium salt solution is room temperature to 90°C and the stirring rate is 100-500rpm, the completely dissolved aluminate solution can be added to the lithium salt solution at a flow rate of 0.02-5L / min through a peristaltic pump, and the amount of aluminate solution added can be 0.38-20L per liter of the lithium salt solution. After the mixing is completed, stirring is continued, and the stirring conditions may include: a stirring rate of 100-500 rpm and a time of 30-120 min; Mixing method 3: the lithium salt solution and the aluminate solution are mixed in a parallel flow manner at a flow rate of 0.02-5 L / min. The flow rates of the lithium salt and the aluminate are calculated based on a mixing reaction in which the molar ratio of Li in the lithium salt to Al in the aluminate is 1-1.3:2.

[0055] Preferably, in step S1, the concentration of the lithium salt solution is 0.5-5 mol / L, and the concentration of the aluminate solution is 0.5-2 mol / L, preferably 4-5 mol / L; the molar ratio of Li in the lithium salt to Al in the aluminate is 1-1.3:2, preferably 1.5-2 mol / L.

[0056] When the lithium salt solution is added to the aluminate solution, the aluminate solution is stirred at 100-500 rpm, and the lithium salt solution is added at a flow rate of 0.02-5 L / min. The amount of the lithium salt solution added can be 0.05-2.6 L per liter of the aluminate solution.

[0057] When the aluminate solution is added to the lithium salt solution, the lithium salt solution can be stirred at 100-500 rpm, and the aluminate solution can be added at a flow rate of 0.02-5 L / min. The amount of the aluminate solution added can be 0.38-20 L per liter of the lithium salt solution.

[0058] The first stirring conditions may include: a stirring time of 30-120 min, a stirring rate of 100-500 rpm, and a temperature of 10 to 90°C, preferably 40-60°C.

[0059] The first aging conditions may include: a temperature of 5-30° C. and a time of 1-12 h, preferably 1-2 h.

[0060] The first filtering conditions may include: the filter cloth mesh number is 1000-5000 mesh, and the filtering negative pressure is 0.04-0.07 MPa.

[0061] Preferably, the method may further comprise: subjecting the filtrate obtained by the first filtration to 1 to 3 rounds of washing and filtration cycles before mixing with the acid; and / or,

[0062] The filtrate obtained by the second filtration is subjected to 1 to 3 rounds of washing and filtration cycle treatment before the pre-desorption-filtration cycle treatment;

[0063] The washing and filtering cycle treatment includes a first washing and a fourth filtering performed in sequence, wherein the first washing is accompanied by stirring; the conditions of the first washing may include: a temperature of 5-30°C, a time of 3-15min, a stirring rate of 100-300rpm, and a weight ratio of the filtrate obtained by the first filtering to pure water of 1:5-50; the conditions of the fourth filtering may include: a filter cloth mesh of 1000-5000 mesh, and a filtering negative pressure of 0.04-0.07MPa. In the present disclosure, the washing and filtering cycle treatment can make the content of impurities such as sodium and potassium in the synthesized adsorbent low, and H + OH - The content is low and the adsorbent is basically neutral, avoiding the presence of acidic or alkaline conditions.

[0064] Preferably, in step S2, the concentration of the acid is 0.5-3 mol / L;

[0065] The second stirring conditions include: stirring time of 30-120 min, stirring rate of 100-500 rpm;

[0066] The second aging conditions include: temperature of 5-30°C, time of 1-12h, preferably 11-12h;

[0067] The conditions for the second filtration include: the mesh number of the filter cloth is 1000-5000 mesh; and the filtration negative pressure is 0.04-0.07 MPa.

[0068] The present invention utilizes lithium salt and aluminate to generate an adsorbent precursor in a one-step process, which has a high conversion rate and is easy to control. An adsorbent with good adsorption performance can be produced in a short period of time, and the production efficiency is high.

[0069] In the present disclosure, the preferred temperature, stirring rate, and stirring time of the washing and filtering cycle treatment can avoid the release of lithium from LiOH·2Al(OH)3·nH2O (n is 1-3) or LiCl·2Al(OH)3·nH2O (n is 1-3), thereby avoiding structural damage. The preferred temperature and time of the aging can also avoid the release of lithium from LiOH·2Al(OH)3·nH2O (n is 1-3) or LiCl·2Al(OH)3·nH2O (n is 1-3), thereby avoiding structural damage; after the aging treatment, the components in the mother liquor that have not been completely reacted can be fully reacted, the suspended matter can be settled, and at the same time, the dissolution of tiny particles promotes the growth of large particles, making the particle size distribution more uniform.

[0070] Preferably, in step S3, the pre-desorption-filtration cycle treatment step may include pre-desorption and third filtration performed in sequence, and the pre-desorption conditions may include: the weight ratio of the second filtrate to the pre-desorbed pure water is 1:5-100; the pre-desorption treatment is accompanied by stirring; the pre-desorption temperature may be 30-50°C, the pre-desorption time may be 2-6h, and the stirring rate may be 100-500rpm;

[0071] The conditions of the third filtration may include: the mesh number of the filter cloth is 1000-5000 mesh; the negative pressure of the filtration is 0.04-0.07 MPa;

[0072] Optionally, the lithium removal amount of the pre-desorption-filtration cycle treatment is 50-80%.

[0073] In the present disclosure, the filtrate obtained by the second filtration, LiCl·2Al(OH)3·nH2O, where n is an integer of 1-3, is in a full lithium state. The lithium in the obtained filtrate can be eluted through the pre-desorption treatment to generate lithium vacancies, thereby having the ability to adsorb lithium. Within the above-mentioned preferred pre-desorption time, it is possible to avoid the adsorption capacity of the adsorbent being insufficiently released due to too low a de-lithium amount; it is also possible to avoid the adsorbent structure being damaged and losing its adsorption capacity due to too high a de-lithium amount.

[0074] Optionally, the method further comprises: drying the filtrate obtained from the pre-desorption-filtration cycle treatment.

[0075] Optionally, the drying conditions include: a temperature of 70-90° C. and a time of 120-180 min.

[0076] In the present disclosure, the drying may be performed using a blast drying oven; the adsorbent is ground or gas-crushed after drying to eliminate powder compaction and make the particles more fine and uniform.

[0077] Particularly preferably, according to one embodiment of the present application, the present application provides a method for preparing a lithium ion adsorbent, the method comprising:

[0078] S1. A 0.5-5 mol / L lithium salt solution is added to a 0.5-2 mol / L metaaluminate solution at a rate of 0.02-5 L / min per liter of the metaaluminate solution under stirring at 100-500 rpm; or a 0.5-2 mol / L metaaluminate solution is added to a 0.5-2 mol / L metaaluminate solution at a rate of 0.02-5 L / min per liter of the lithium salt solution under stirring at 100-500 rpm. mol / L lithium salt solution; then, a first stirring is performed at a stirring rate of 100-500 rpm and a temperature of 10 to 90° C. for 30-120 min, a first aging is performed at a temperature of 5-30° C. for 1-12 h, and a first filtration is performed at a filter cloth mesh number of 1000-5000 mesh and a filtration negative pressure of 0.04-0.07 MPa to obtain a precursor of a substance having a chemical formula of LiOH·2Al(OH)3·nH2O, where n is an integer of 1-3;

[0079] S2, subjecting the filtrate obtained by the first filtration to 1-3 rounds of washing and filtering cycle treatment, wherein the washing and filtering cycle treatment includes a first washing and a fourth filtration performed in sequence, wherein the filtrate obtained by the first filtration is subjected to a first washing for 3-15 minutes at a temperature of 30-50° C. and a stirring rate of 100-300 rpm at a weight ratio of 1:5-50 for the filtrate and pure water, and then subjected to a first washing for 3-15 minutes at a filter cloth mesh number of 1000-5000 mesh and a filtration negative pressure of 0.04-0.07 MPa. Fourth filtration: mixing the precursor treated by washing and filtering cycles with an acid, and controlling the amount of the acid added so that the pH value of the mixed material is 6.0-7.0; performing a second stirring for 30-120 min at a stirring rate of 100-500 rpm, performing a second aging for 1-12 h at a temperature of 5-30° C., and performing a second filtration at a filter cloth mesh number of 1000-5000 mesh and a filtration negative pressure of 0.04-0.07 MPa to obtain a filtrate of the second filtration;

[0080] S3, subjecting the filtrate obtained by the second filtration to 1 to 3 rounds of washing and filtering cycle treatment, wherein the washing and filtering cycle treatment includes a first washing and a fourth filtration performed in sequence, wherein the filtrate obtained by the second filtration is subjected to a first washing for 3-15 minutes at a temperature of 30-50° C. and a stirring rate of 100-300 rpm at a weight ratio of 1:5-50 for the filtrate to pure water, and then subjected to a fourth filtration at a filter cloth mesh number of 1000-5000 mesh and a filtration negative pressure of 0.04-0.07 MPa; and then The filtrate obtained by the second filtration of the washing and filtering cycle treatment is subjected to 1 to 3 rounds of pre-desorption-filtration cycle treatment; the steps of the pre-desorption-filtration cycle treatment include pre-desorption and third filtration performed in sequence, the filtrate obtained by the second filtration and the pre-desorbed pure water are pre-desorbed for 2-6 hours at a weight ratio of 1:5-100, at a temperature of 30-50°C and a stirring rate of 100-500rpm, and the filter cloth mesh number is 1000-5000 mesh; the third filtration is performed under the condition of a filtration negative pressure of 0.04-0.07MPa.

[0081] The present disclosure is further illustrated by the following examples, but the present disclosure is not limited thereby.

[0082] Example 1

[0083] 500 ml of 0.5 mol / L lithium chloride solution was added to 1000 ml of 0.5 mol / L sodium aluminate solution through a peristaltic pump at a flow rate of 20 ml / min, and the mixture was first stirred at a stirring rate of 300 rpm for 30 min at room temperature, and first aged for 1 h at room temperature, and a precursor was obtained by a first filtration. The precursor obtained by the first filtration was added with pure water at a weight ratio of 1:5 to the precursor, and then washed and filtered in a cycle, and the precursor was first washed at 300 rpm for 3 min, and then filtered out by a fourth filtration. The precursor was tested by XRD, and the results showed that it contained LiAl2(OH)7·1.5H2O. 0.5 mol / L HCl was added to the precursor at a weight ratio of 1:1, the pH value was adjusted to 6.5, a second stirring was performed at a stirring rate of 300 rpm for 30 minutes, a second aging was performed at room temperature for 1 hour, and a filtrate of the second filtration was obtained by a second filtration; the filtrate obtained by the second filtration was added with pure water at a weight ratio of 1:5 to pure water for a washing and filtering cycle treatment, a first washing was performed at 300 rpm for 3 minutes, and a filtrate was obtained by a fourth filtration; the filtrate obtained by filtration was added with pure water at a weight ratio of 1:5 to pure water, a pre-desorption treatment was performed at 30°C and a stirring rate of 300 rpm for 2 hours, and after the pre-desorption treatment, a third filtration was performed, and the filtrate obtained by the third filtration was dried at 80°C for 2 hours to obtain a lithium adsorbent.

[0084] Example 2

[0085] 50 ml of 5 mol / L lithium chloride solution was added to 250 ml of 2 mol / L sodium aluminate solution through a peristaltic pump at a flow rate of 20 ml / min, and the mixture was first stirred at a stirring rate of 300 rpm for 30 min at room temperature, and first aged for 1 h at room temperature, and a precursor was obtained by a first filtration; the precursor obtained by the first filtration was added with pure water at a weight ratio of 1:5 to the precursor, and a washing and filtering cycle was performed, and the first washing was performed at 300 rpm for 3 min, and the precursor was filtered out by a fourth filtration. The precursor was tested by XRD, and the results showed that it contained LiAl2(OH)7·2H2O. 0.5 mol / L HCl was added to the precursor at a weight ratio of 1:1, the pH value was adjusted to 6-7, a second stirring was performed at a stirring rate of 300 rpm for 30 minutes, a second aging was performed at room temperature for 1 hour, and a filtrate of the second filtration was obtained by a second filtration; the filtrate obtained by the second filtration was added with pure water at a weight ratio of 1:5 to pure water for a washing and filtering cycle treatment, a first washing was performed at 300 rpm for 3 minutes, and a filtrate was obtained by a fourth filtration; the filtrate obtained by filtration was added with pure water at a weight ratio of 1:5 to pure water, a pre-desorption treatment was performed at 30°C and a stirring rate of 300 rpm for 2 hours, and after the pre-desorption treatment, a third filtration was performed, and the filtrate obtained by the third filtration was dried at 80°C for 2 hours to obtain a lithium adsorbent.

[0086] Example 3

[0087] 50 ml of 5 mol / L lithium chloride solution was added to 250 ml of 2 mol / L sodium aluminate solution through a peristaltic pump at a flow rate of 20 ml / min, and the mixture was first stirred at a stirring rate of 300 rpm for 30 min at 50 ° C, and first aged at room temperature for 1 h. A precursor was obtained by a first filtration. The precursor obtained by the first filtration was added with pure water at a weight ratio of 1:5 to pure water for washing and filtering cycle treatment, and the first washing was carried out at 300 rpm for 3 min. The precursor was filtered out by a fourth filtration, and the precursor was tested by XRD, and the results showed that it contained LiAl2(OH)7·2H2O. 0.5 mol / L HCl was added to the precursor at a weight ratio of 1:1, the pH value was adjusted to 6.5, a second stirring was performed at a stirring rate of 300 rpm for 30 minutes, a second aging was performed at room temperature for 1 hour, and a filtrate of the second filtration was obtained by a second filtration; the filtrate obtained by the second filtration was added with pure water at a weight ratio of 1:5 to pure water for a washing and filtering cycle treatment, and after the first washing for 3 minutes at 300 rpm, a filtrate was obtained by a fourth filtration; the filtrate obtained by filtration was added with pure water at a weight ratio of 1:5 to pure water, and a pre-desorption treatment was performed at 30°C and a stirring rate of 300 rpm for 2 hours. After the pre-desorption treatment, the filtrate was filtered for a third time, and the filtrate obtained by the third filtration was dried at 80°C for 2 hours to obtain a lithium adsorbent.

[0088] Example 4

[0089] 50 ml of 5 mol / L lithium chloride solution was added to 250 ml of 2 mol / L sodium aluminate solution through a peristaltic pump at a flow rate of 20 ml / min, and the mixture was first stirred at a stirring rate of 300 rpm for 30 min at 50 °C, and first aged at room temperature for 2 h. A precursor was obtained by a first filtration. The precursor obtained by the first filtration was added with pure water at a weight ratio of 1:5 to pure water for a washing cycle. After the first washing was carried out at 300 rpm for 3 min, the precursor was filtered out by a fourth filtration. The precursor was tested by XRD, and the results showed that it contained LiAl2(OH)7·2H2O. 0.5 mol / L HCl was added to the precursor at a weight ratio of 1:1, the pH value was adjusted to 6.5, a second stirring was performed at a stirring rate of 300 rpm for 30 minutes, a second aging was performed at room temperature for 12 hours, and a filtrate of the second filtration was obtained by a second filtration; the filtrate obtained by the second filtration was added with pure water at a weight ratio of 1:5 to pure water for a washing and filtering cycle treatment, a first washing was performed at 300 rpm for 3 minutes, and a filtrate was obtained by a fourth filtration; the filtrate obtained by filtration was added with pure water at a weight ratio of 1:5 to pure water, a pre-desorption treatment was performed at 30°C and a stirring rate of 300 rpm for 2 hours, and after the pre-desorption treatment, a third filtration was performed, and the filtrate obtained by the third filtration was dried at 80°C for 2 hours to obtain a lithium adsorbent.

[0090] Comparative Example 1

[0091] 21.2 g of anhydrous lithium chloride and 133.3 g of anhydrous aluminum chloride were dissolved in 1 L of deionized water and then added to 1.5 L of 2 mol / L sodium bicarbonate solution. The mixture was reacted at 65 °C for 1 h to obtain a suspension containing LiCl·2Al(OH)3·nH2O. After solid-liquid separation, the lithium chloride was eluted with deionized water and dried at 90 °C for 12 h to obtain an adsorbent.

[0092] Comparative Example 2

[0093] 156 g of 400 mesh Al(OH)3 particles were added to 1 L of 1 mol / L LiOH solution and reacted at 80 °C for 12 h to allow LiOH to fully penetrate the gaps between the Al(OH)3 particles. Then, 1 mol / L HCl was added to adjust the pH value of the solution to 6.5. After aging at room temperature for 24 h, LiCl·2Al(OH)3·nH2O was prepared.

[0094] Example 5

[0095] This example is used to illustrate the adsorption performance test results

[0096] Take lithium-containing brine with high magnesium-lithium ratio for testing, Li +The concentration is 0.02333wt%, Mg 2+ The concentration is 7.8540wt%, and the mass ratio of magnesium to lithium in the brine is 337:1. Weigh 10g of adsorbent and adsorb it at a ratio of 1:50 at room temperature. The stirring rate is 300rpm and the adsorption time is 90min. After adsorption, filter and rinse at the same time, and the amount of rinsing water is 250mL. After elution, desorb with pure water at a solid-liquid ratio of 1:10, the stirring rate is 300rpm, the temperature is 35℃, and the desorption time is 60min. The measured adsorption capacity is the working adsorption capacity of the adsorbent.

[0097] Table 1 shows the specific surface area, pore size, pore volume and particle size data of the synthetic adsorbents of Examples 1, 2, 3, 4 and Comparative Examples 1 and 2.

[0098] Table 1

[0099]

[0100]

[0101] The adsorbent synthesized in Examples 1-4 has a large specific surface area, a small pore size, a large total pore volume, a high porosity, and a uniform particle size distribution. Compared with Example 1, Example 2 increases the reactant concentration of the mixed precipitation reaction, increases the specific surface area of ​​the synthesized adsorbent, and reduces the particle size; Compared with Example 2, Example 3 increases the temperature of the precipitation reaction, further reduces the adsorbent particle size, increases the specific surface area, reduces the pore size, increases the total pore volume, and increases the porosity. Compared with Example 3, Example 4 prolongs the aging time, and the particle size distribution is more uniform. In the case where the concentration of the lithium salt solution is preferably 4-5 mol / L, the concentration of the aluminate solution is 1.5-2 mol / L, the temperature of the first stirring is 40-60°C, the first aging time is 1-2h, and the second aging time is 11-12h, the adsorbent has a more preferred specific surface area, particle size, pore size, total pore volume, porosity, and particle size distribution. The specific surface area, pore size, and porosity of the synthesized adsorbent in Comparative Example 1 are similar to those in Example 2, but the uniformity of the particle size distribution is poor. The synthetic adsorbent of Comparative Example 2 has a small specific surface area, a large pore size, a low porosity, and the particle size and particle size distribution are greatly affected by the Al(OH)3 raw material.

[0102] Table 2 shows the Li adsorption of the synthetic adsorbents of Examples 1, 2, 3, 4 and Comparative Examples 1 and 2. + Concentration wt%, Li + Adsorption capacity mg / g, desorption liquid Li + Concentration wt%, Li + Desorption rate %, desorption liquid Mg 2+Concentration wt%, desorption solution magnesium-lithium ratio and adsorption capacity mg / g data after 50 cycles.

[0103] Table 2

[0104]

[0105]

[0106] The adsorbents synthesized in Examples 1-4 have high adsorption-desorption efficiency, large adsorption capacity, high lithium selectivity, stable adsorbent structure, and good cycle stability. By comparing Examples 1, 2, 3 and 4, the results show that increasing the concentration of the reactants of the precipitation reaction, raising the precipitation reaction temperature, and extending the aging time are beneficial to increasing the specific surface area and porosity of the adsorbent, reducing the pore size, and thus improving the adsorption capacity and lithium selectivity. When the concentration of the lithium salt solution is preferably 4-5 mol / L, the concentration of the aluminate solution is 1.5-2 mol / L, the temperature of the first stirring is 40-60°C, the first aging time is 1-2h, and the second aging time is 11-12h, the adsorbent has a more preferred adsorption capacity, lithium selectivity, structural stability and cycle stability. The adsorbents synthesized in Comparative Examples 1 and 2 have low adsorption capacity, and the desorption efficiency of Comparative Example 2 is low, and the lithium selectivity is low.

[0107] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0108] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0109] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A lithium ion adsorbent, characterized in that: The lithium ion adsorbent contains a chemical formula of LiCl·2Al(OH)3· n H2O substances, among which, n An integer from 1 to 3; The specific surface area of ​​the lithium ion adsorbent is 20-36m 2 / g; The average pore diameter of the lithium ion adsorbent is 20-35 nm; The total pore volume of the lithium ion adsorbent is 0.15-0.32 mL / g; The D10 of the lithium ion adsorbent is 3-12 μm; The D50 of the lithium ion adsorbent is 12-22 μm; The D90 of the lithium ion adsorbent is 20-40 μm.

2. The lithium ion adsorbent according to claim 1, wherein The specific surface area of ​​the lithium ion adsorbent is 33-36m 2 / g; The average pore diameter of the lithium ion adsorbent is 22-24 nm; The total pore volume of the lithium ion adsorbent is 0.28-0.32 mL / g; The D10 of the lithium ion adsorbent is 3-6 μm; The D50 of the lithium ion adsorbent is 12-16 μm; The D90 of the lithium ion adsorbent is 20-29 μm.

3. The lithium ion adsorbent according to claim 1, wherein The lithium ion adsorption capacity of the lithium ion adsorbent is 3-10 mg / g; The lithium ion desorption rate of the lithium ion adsorbent is 95-100%; When the lithium ion adsorbent is used for adsorbing lithium ions in brine containing magnesium and lithium, the mass ratio of magnesium to lithium in the brine to the mass ratio of magnesium to lithium in the desorption solution is 18-68:1; The lithium ion adsorbent has a chemical formula of LiCl·2Al(OH)3· n The substance content of H2O is 95-100% by weight.

4. The lithium ion adsorbent according to claim 3, wherein The lithium ion adsorption capacity of the lithium ion adsorbent is 8-10 mg / g; The lithium ion desorption rate of the lithium ion adsorbent is 98-99%.

5. A method for preparing a lithium ion adsorbent, characterized in that: The method comprises the following steps: S1, adding a lithium salt solution to a metaaluminate solution, or adding a metaaluminate solution to a lithium salt solution, and then performing a first stirring, a first aging and a first filtration to obtain a solution having a chemical formula of LiOH·2Al(OH)3· n Precursor of H2O, n An integer from 1 to 3; S2, mixing the precursor with an acid, and controlling the amount of the acid added so that the pH value of the mixed material is 6.0-7.0, and then performing a second stirring, a second aging, and a second filtration to obtain a filtrate of the second filtration; S3, subjecting the filtrate of the second filtration to 1 to 3 rounds of pre-desorption-filtration cycle treatment; The concentration of the lithium salt solution is 0.5-5 mol / L, and the concentration of the aluminate solution is 0.5-2 mol / L; the molar ratio of Li in the lithium salt to Al in the aluminate is 1-1.3:2; The first stirring conditions include: stirring time of 30-120 min, stirring rate of 100-500 rpm, and temperature of 10 to 90° C.; The first aging conditions include: temperature of 5-30°C and time of 1-12h; The second stirring conditions include: stirring time of 30-120 min, stirring rate of 100-500 rpm; The second aging conditions include: temperature of 5-30°C and time of 1-12h.

6. The method according to claim 5, wherein: In step S1, the concentration of the lithium salt solution is 4-5 mol / L, and the concentration of the aluminate solution is 1.5-2 mol / L; When the lithium salt solution is added to the aluminate solution, the aluminate solution is stirred at 100-500 rpm, and the lithium salt solution is added at a flow rate of 0.02-5 L / min, and the amount of the lithium salt solution added is 0.05-2.6 L per liter of the aluminate solution; When the metaaluminate solution is added to the lithium salt solution, the lithium salt solution is stirred at 100-500 rpm, and the metaaluminate solution is added at a flow rate of 0.02-5 L / min, and the amount of the metaaluminate solution added is 0.38-20 L per liter of the lithium salt solution; The first stirring conditions include: a temperature of 40-60°C; The first aging conditions include: a time of 1-2 hours; The conditions for the first filtration include: the mesh number of the filter cloth is 1000-5000 mesh, and the filtration negative pressure is 0.04-0.07 MPa.

7. The method according to claim 5, wherein: The method further comprises: subjecting the filtrate obtained from the first filtration to 1 to 3 rounds of washing and filtration cycles before mixing with the acid; and / or, The filtrate obtained by the second filtration is subjected to 1 to 3 rounds of washing and filtration cycle treatment before the pre-desorption-filtration cycle treatment; The washing and filtering cycle treatment includes a first washing and a fourth filtration performed in sequence, wherein the first washing is accompanied by stirring; the conditions of the first washing include: a temperature of 5-30°C, a time of 3-15min, a stirring rate of 100-300rpm, and a weight ratio of the filtrate obtained by the first filtration to pure water of 1:5-50; the conditions of the fourth filtration include: a filter cloth mesh number of 1000-5000 meshes, and a filtration negative pressure of 0.04-0.07MPa.

8. The method according to claim 5, wherein: In step S2, the concentration of the acid is 0.5-3 mol / L; The second stirring conditions include: stirring time of 30-120 min, stirring rate of 100-500 rpm; The second aging conditions include: a time of 11-12 hours; The conditions for the second filtration include: the mesh number of the filter cloth is 1000-5000 mesh; and the filtration negative pressure is 0.04-0.07 MPa.

9. The method according to claim 5, wherein: In step S3, the pre-desorption-filtration cycle treatment step includes pre-desorption and third filtration performed in sequence, and the pre-desorption conditions include: the weight ratio of the filtrate of the second filtration to the pure water of the pre-desorption is 1:5-100; the pre-desorption treatment is accompanied by stirring; the temperature is 30-50°C, the time is 2-6h, and the stirring rate is 100-500rpm; The conditions for the third filtration include: the mesh number of the filter cloth is 1000-5000 mesh; the filtration negative pressure is 0.04-0.07 MPa.

10. The method according to claim 5, wherein: The lithium removal amount of the pre-desorption-filtration cycle treatment is 50-80%.

11. The method according to claim 5, wherein: The method further comprises: drying the filtrate obtained from the pre-desorption-filtration cycle treatment.

12. The method according to claim 11, wherein: The drying conditions include: temperature of 70-90° C. and time of 120-180 min.

Citation Information

Patent Citations

  • Lithium adsorbent, preparation method and applications thereof, and method for extracting lithium from lithium-containing solution

    CN110102273A

  • Aluminum-based lithium ion sieve as well as preparation method and application thereof

    CN112808226A